Effect of Processing Variables on the Sensory Quality of Milkcake - KUMAR, ANIL; Patil, Girdhari Ramdas; Singh, Ram Ran Bijoy; Patel, Ashok Ambalal (Indian Journal of Dairy Science, 2014)
Sensory quality of milkcake as a function of processing variables was evaluated to standardize the process for manufacturing long-life milkcake. Different levels of processing variables that were studied included fat percentage (4-6%) in milk, levels of sugar (8-12%) and corn syrup (0-6%) and thermization temperature (60 to 80Â°C for 60 min.). The sensory parameters studied were flavour, body & texture, colour & appearance and overall acceptability. The sugar and corn syrup levels and thermization temperature were found to significantly (p<0.01) affect all the sensory parameters while the effect of fat percentage in milk was not significant on colour and appearance of the product but significant (p<0.01) for other sensory parameters. It was concluded that the levels of fat in milk at 5%, sugar at 10%, corn syrup at 2% and thermization temperature of 75Â°C/60 min were optimum for the preparation of milkcake with best sensory quality.